WISATA AGRIBISNIS SEBAGAI PRODUK PENGEMBANGAN USAHA INTELEKTUAL KAMPUS - Hartati; Ahmad Muhlis Nuryadi; Herdianto Husein (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2023)
Agribusiness Tourism is a business managed by maximizing tourism-based culinary business activities. The main objective of these community activities is to accelerate the process of developing entrepreneurship oriented to local culinary products. This effort involves students of the Agribusiness Study Program Faculty of Agriculture and Management Study Program, Faculty of Economics and Islamic Business (FEBI). This activity provides experience and job opportunities for students open employment opportunities for the community and provide culinary needs in the form of traditional foods of Southeast Sulawesi (sinonggi) and healthy, fresh and delicious seafood for customers. The method of carrying out the activities consists of socializing, training, providing infrastructure and facilities, promotion, and marketing. This activity is carried out in the area of ​​embankments that were previously less productive with relatively low income. The location is in the Poasia District of Kendari, Southeast Sulawesi. To accelerate the process of developing entrepreneurship, the activity is designed by changing a traditional embankment into an agribusiness tourism specific to local culinary tourism by designing a gazebo building as a place to enjoy culinary menu orders. The location has its characteristics with the design of the place based on agribusiness decorated with ornamental plants, pollution-absorbing plants, hydroponic plants, and organic vegetable plants. Visitors can enjoy the natural scenery through the embankment garden design in the form of selfie spots for visitors. The results of the implementation of the activity are in the form of a business unit "Culinary Tourism" based on culinary tourism has been opened since June 2019 by providing sinonggi menu packages and various seafood products.  ---  Wisata Agribisnis merupakan usaha yang dikelola dengan memaksimalkan kegiatan bisnis kuliner berbasis wisata. Tujuan utama pelaksanaan kegiatan masyarakat ini adalah mempercepat proses pengembangan kewirausahaan yang berorientasi pada produk kuliner lokal. Usaha ini melibatkan mahasiswa Program Studi Agribisnis, Fakultas Pertanian dan Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Islam (FEBI). Kegiatan ini  memberi pengalaman dan kesempatan kerja bagi mahasiswa, membuka lapangan kerja bagi masyarakat serta menyediakan kebutuhan kuliner berupa makanan tradional khas Sulawesi Tenggara  (sinonggi) dan sea food yang sehat, segar dan nikmat bagi pelanggan. Metode pelaksanaan kegiatan terdiri dari sosialisasi, pelatihan dan penyediaan prasarana dan sarana, promosi serta pemasaran. Kegiatan ini dilaksanakan di areal tambak yang sebelum nya kurang produktif dengan pendapatan yang relatif rendah. Lokasi berada di Kecamatan Poasia Kota Kendari Sulawesi Tenggara. Hasil pelaksanaan kegiatan ditujukan untuk percepatan proses pengembangan kewirausahaan. Kegiatan di desain dengan mengubah tambak tradisional menjadi sebuah wisata agribisnis spesifik wisata kuliner lokal. Lokasi mempunyai ciri khas tersendiri dengan desain bangunan gasebo berbasis agribisnis dengan dihiasi tanaman hias, tanaman penyerap polusi, tanaman hidroponik dan tanaman sayuran organik. Pengunjung dapat menikmati pemandangan alam melalui desain taman tambak berupa spot selfi bagi pengunjung. Hasil pelaksanaan kegiatan adalah terbentuk satu unit usaha ”Wisata Agibisnis” berbasis wisata kuliner yang telah resmi dibuka  sejak juni 2019 sampai sekarang dengan menyediakan produk paket menu sinonggi dan aneka sea food.